Strategic communication to overcome challenges in digital literacy policy implementation in Japan Schools - Boonwattanopas, Dhanikcha (Jurnal Kajian Komunikasi, 2025)
Background: The Japanese government has initiated a national policy to improve digital literacy in elementary schools, but its implementation still faces various challenges, such as disparities between regions, limited infrastructure, and the readiness of educators to teach digital literacy effectively. Purpose: This study aims to analyze communication strategies in the implementation of digital literacy policies in elementary schools in Japan. Methods:  The research used a qualitative case study approach in several elementary schools in the Tokyo metropolitan area. Data were collected through in-depth interviews with key informants using a purposive approach. Result: The results show that the implementation of digital literacy policies has not been uniform across elementary schools in Japan. The main barriers found include a lack of teacher training, limited digital infrastructure and a lack of systematic communication strategies. Schools in urban areas of Japan are more advanced in implementing the policy compared to schools in rural areas of Japan. However, some schools managed to overcome these challenges through strategic communication and collaboration with parents, communities, and the technology sector, as well as utilizing social media and digital platforms.  Conclusion: This study emphasizes the importance of more systematic and inclusive communication strategies in the implementation of digital literacy policies. Effective communication between the government, schools, teachers, and parents plays a role in increasing understanding and participation in this policy. Implications: This study opens up opportunities for further exploration of the effectiveness of different communication methods, such as digital platforms, social media, and face-to-face approaches.